(untitled) (Journal of the College of Education for Women, 2019)
Preparing teacher occupies the attention of many thinkers and philosophers since the age ofkaldinics ( people of mesoptam / 2342 pH ) to the Islamic age where moslems philosophersfocus their attention on thought and philosophy where the philosophy of that teachingdepends on : teacher , student and family begin .So , the issue of preparing and training teacher occupies the attention of education scientistsdepending on his vital and important role in implementing of teaching policies in philosophiesand Islamic educational thought , therefore , the preparing and development of the teacherregards as one of the basics of teaching development because of its importance indevelopment of teaching performance and the industrial development is the key of acquiringacademic skills by the teacher by direct activities of the formal training programs or by selfteaching technique .Teacher regards one of the most important agents of educational process because he has theability of achieving the teaching goals and development of the skills of students by arrangingthe teaching process and using its teaching techniques and recognizing the students needs and their thinking ways and recognizing the aims of education in development of society whereteacher known as ( the one who teaches students ,the bridge connecting the school and society, holder of message which make him special one in society where some people make him as aprophet and the one who owns the wide educational abilities helping him in recognizing thegoals and the matters and the best using of the methods of teaching where we can call him asan engineer of educational process and finally as decision maker .The ability of coping with rapid new technology depends on the teacher who has the abilityof teaching the new methods and strategies of teaching and their application where he cantransfer this thought to his students by using the educational teaching methods, so, theeducational teaching is not as soft wares or interesting devices but a teacher owns thespecification which help him in applying the techniques in educational process.The present paper aims at recognizing the importance of active teacher and his role in thedevelopment of curriculums by using educational technology, the paper reaches at results andrecommendation.